Downregulation of the ypdA Gene Encoding an Intermediate of His-Asp Phosphorelay Signaling in Aspergillus nidulans Induces the Same Cellular Effects as the Phenylpyrrole Fungicide Fludioxonil - Yoshimi, Akira; Hagiwara, Daisuke; Ono, Miyako; Fukuma, Yasuyuki; Midorikawa, Yura; Furukawa, Kentaro; Fujioka, Tomonori; Mizutani, Osamu; Sato, Natsuko; Miyazawa, Ken; Maruyama, Jun-ichi; Marui, Junichiro; et al. (Frontiers in Fungal Biology, 2021)
Many eukaryotic histidine-to-aspartate (His-Asp) phosphorelay systems consist of three types of signal transducers: a His-kinase (HK), a response regulator (RR), and a histidine-containing phosphotransfer intermediate (HPt). In general, the HPt acts as an intermediate between the HK and the RR and is indispensable for inducing appropriate responses to environmental stresses. In a previous study, we attempted but were unable to obtain deletion mutants of the ypdA gene in order to characterize its function in the filamentous fungus Aspergillus nidulans. In the present study, we constructed the CypdA strain in which ypdA expression is conditionally regulated by the A. nidulans alcA promoter. We constructed CypdA strains with RR gene disruptions (CypdA-sskA∆, CypdA-srrA∆, and CypdA-sskA∆srrA∆). Suppression of YpdA induced by ypdA downregulation activated the downstream HogA mitogen-activated protein kinase cascade. YpdA suppression caused severe growth defects and abnormal hyphae, with features such as enhanced septation, a decrease in number of nuclei, nuclear fragmentation, and hypertrophy of vacuoles, both regulated in a SskA–dependent manner. Fludioxonil treatment caused the same cellular responses as ypdA suppression. The growth-inhibitory effects of fludioxonil and the lethality caused by ypdA downregulation appear to be caused by the same or similar mechanisms and to be dependent on both the SskA and SrrA pathways.